Integrating YouTube into Project-Based Learning to Enhance Students’ Interest in Islamic Religious Education at a Vocational Secondary School - Agustina, Dwi; Syafe’i, Imam; Baharudin, Baharudin; Wahyudi, Didik (MAN 4 Kota Pekanbaru, 2026)
This study examines the effectiveness of integrating YouTube-based Project-Based Learning (PjBL) to enhance students’ interest in Islamic Religious Education (IRE). A quasi-experimental post-test-only control group design was employed, involving tenth-grade students at SMK Geomatika Lampung, a vocational secondary school in Indonesia. Students’ learning interest was measured using a validated Likert-scale questionnaire, and the data were analyzed through normality, homogeneity, and independent samples t-tests. The findings revealed a statistically significant difference in learning interest between students taught using YouTube-based PjBL and those taught through conventional methods (p < 0.05). The integration of project-based learning with digital video media promoted active engagement, motivation, and positive affective responses in IRE learning. However, since the study was conducted in a single vocational school context, the findings should be interpreted cautiously and may not be generalized to all vocational secondary schools without further empirical validation. Future research involving broader and more diverse samples is recommended to strengthen generalizability.